Hyperinsulinemic Hypoglycemia – The Molecular Mechanisms - Nessa, Azizun; Rahman, Sofia A.; Hussain, Khalid (Frontiers in Endocrinology, 2016)
Under normal physiological conditions pancreatic β-cells secrete insulin to maintain fasting blood glucose levels in the range 3.5-5.5mmol/L. In hyperinsulinaemic hypoglycaemia (HH) this precise regulation of insulin secretion is perturbed so that insulin continues to be secreted in the presence of hypoglycaemia. HH may be due to genetic causes (congenital) or secondary to certain risk factors. The molecular mechanisms leading to HH involve defects in the key genes regulating insulin secretion from the β-cells. At this moment in time genetic abnormalities in 9 genes (ABCC8, KCNJ11, GCK, SCHAD, GLUD1, SLC16A1, HNF1A, HNF4A and UCP2) have been described that lead to the congenital forms of HH. Perinatal stress, intrauterine growth retardation, maternal diabetes mellitus and a large number of developmental syndromes are also associated with HH in the neonatal period. In older children and adult’s insulinoma, Noninsulinoma pancreatogenous hypoglycaemia syndrome and post bariatric surgery are recognised causes of HH. This review article will focus mainly on describing the molecular mechanisms that lead to unregulated insulin secretion.